A neurofeedback video game (MindLight) to prevent anxiety in children: A randomized controlled trial. (October 2016) - Schoneveld, Elke A.; Malmberg, Monique; Lichtwarck-Aschoff, Anna; Verheijen, Geert P.; Engels, Rutger C.M.E.; Granic, Isabela
Abstract: Background: Childhood anxiety is a global mental health concern. Interventions are needed that are effective, but also cost less, are more accessible and engage children long enough to build emotional resilience skills through practice. Methods: The present randomized controlled study aimed to examine the prevention effects of a neurofeedback video game, MindLight, developed based on evidence-based practices with anxious youth. Over 750 children (7–13 years old) in elementary schools were screened for elevated anxiety; 136 selected children were randomly assigned to play Mindlight or a control game. Self- and parent-reported anxiety was assessed at pre-, post-intervention and 3-month follow up. Results/conclusions: Intent-to-treat analyses revealed an overall significant reduction in child- and parent-reported anxiety, but the magnitude of improvements did not differ between conditions. Future research comparing MindLight to cognitive-behavioral interventions is suggested, as well as testing a range of specific (e.g., exposure) and non-specific (e.g., expectations, motivation) therapeutic factors as mediators of outcomes.